AERIAL SILK ACROBATICS, INTERFERENCE OF ITS PRACTICE IN THE CONTROL OF EMOTIONAL STRESS. (Fiep Bulletin - online, 2011)
It is known that physical activity produces both physical and psychological benefits may be used as an adjuvant in the control or treatment of symptoms of emotional stress, since practiced correctly. Nowadays stress is considered one of the major problems that cause disease and can now be considered a public health problem. Aerial Silk Acrobatics is an activity that by having great beauty and plasticity, and provide a working muscle and flexibility so valued by its practitioners, has been spread in different places outside of circus. Practitioners often have great satisfaction and motivation in the face of challenges, seeking to overcome them with great commitment and persistence. This study aims to investigate the possible influence of the practice of this activity in controlling symptoms of emotional distress in an adult population. To this end, a descriptive survey was developed and implemented qualitative and quantitative approaches into four spaces Aerial Silk Acrobatics located in Rio de Janeiro (capital). The results from the analysis of percentage, this sample suggest a positive indication as to influence the practice of Aerial Silk Acrobatics in controlling symptoms of emotional stress.
Keywords: Aerial Silk Acrobatics; Stress